2005
DOI: 10.1007/s00203-005-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the orf1glnKamtB operon of Herbaspirillum seropedicae

Abstract: Herbaspirillum seropedicae is an endophytic nitrogen-fixing bacterium that colonizes economically important grasses. In this organism, the amtB gene is co-transcribed with two other genes: glnK that codes for a PII-like protein and orf1 that codes for a probable periplasmatic protein of unknown function. The expression of the orf1glnKamtB operon is increased under nitrogen-limiting conditions and is dependent on NtrC. An amtB mutant failed to transport methylammonium. Post-translational control of nitrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…and H. seropedicae is that in the former the nitrogenase switch-off involves reversible ADP-ribosylation by the DraT and DraG enzymes (Martin and Reinhold-Hurek, 2002). In H. seropedicae the nitrogenase switch off/on occurs through an as yet unknown mechanism of post-translational regulation which involves the ammonia channel AmtB (Noindorf et al, 2006). The wild type switch-off phenotype of the fdxA mutant of H. seropedicae may be explained by the distinct mechanisms for nitrogenase post-translational control.…”
Section: Mutation and Phenotypic Analysis Of The Ferredoxin Genes Of mentioning
confidence: 92%
“…and H. seropedicae is that in the former the nitrogenase switch-off involves reversible ADP-ribosylation by the DraT and DraG enzymes (Martin and Reinhold-Hurek, 2002). In H. seropedicae the nitrogenase switch off/on occurs through an as yet unknown mechanism of post-translational regulation which involves the ammonia channel AmtB (Noindorf et al, 2006). The wild type switch-off phenotype of the fdxA mutant of H. seropedicae may be explained by the distinct mechanisms for nitrogenase post-translational control.…”
Section: Mutation and Phenotypic Analysis Of The Ferredoxin Genes Of mentioning
confidence: 92%
“…In this organism, all genes coding proteins involved in nitrogen metabolism were identified, including glnB, glnK, glnD, ntrB, ntrC and nifA (Souza et al 1991;Benelli et al 1997;Pedrosa et al 2001Pedrosa et al , 2011Noindorf et al 2006). Previous work showed that the H. seropedicae PII proteins GlnB and GlnK are uridylylated in vitro by GlnD.…”
Section: Introductionmentioning
confidence: 97%
“…In this organism two PII-like coding genes were identified, glnB and glnK [14,15]. The glnB gene is monocistronic and its expression is constitutive [14], whereas glnK is apparently co-transcribed with amtB and orf1 , which encode for an ammonium transporter and a membrane associated protein of unknown function, respectively [15]. Recently orf1 was named nlmA ( n itrogen l imitation m embrane protein A) since its product was detected in membrane extracts of H. seropedicae grown under nitrogen-limitation conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently orf1 was named nlmA ( n itrogen l imitation m embrane protein A) since its product was detected in membrane extracts of H. seropedicae grown under nitrogen-limitation conditions [16]. The expression of the nlmAglnKamtB operon is dramatically increased under nitrogen-limiting conditions and is dependent on NtrC [15]. As in other Proteobacteria , both PII proteins from H. seropedicae are targets of covalent modification by GlnD (uridylyl-transferase/uridylyl removing enzyme) in response to the levels of ammonium ions [17].…”
Section: Introductionmentioning
confidence: 99%